Indonesia’s State Enterprises: from State Leadership to International Consensus - Sungkar, Yasmin (Journal of Indonesian Social Sciences and Humanities, 2008)
The survival of state-owned enterprises and continued investment by the state was assisted by high rates of economic growth in Indonesia throughout the 1980s. The currency crisis in the region, which began in mid-1997, destroyed the expectation that rapid growth would continue. In this climate, the loss-making state companies were a serious financial burden, and privatisation has been promoted as a quick solution. It appears that the crisis reintroduced momentum for reform in the huge state-enterprise sector. In response to IMF pressure and its own fiscal difficulties, the government took several measures to reform the state sector. The economic crisis provided a catalyst because it forced the government to assess more seriously the value of state companies. There was an urgent need to sell state-owned assets to relieve the state budget when economic recovery slowed. This paper examines the efforts to reform the state sector during ten years of Reformasi, including the debate over privatisation and the emergence of strong resistance to reform. It appears that the crisis has strengthened the hand of reformers seeking to privatise the state sector. However, despite the logic of government efforts to reform inefficient state companies, there has been a battle with each step towards privatisation.